Pengaruh Pengajaran dan Aktifitas dalam Organisasi terhadap Kreativitas Belajar dengan Variabel Mediasi Psikoedukasi Kreativitas - Ahmad Jalalluddin Al-Mahali (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
Some learning strategies fail to arouse student creativity in learning. Concerns about accountability narrow flexibility and creativity in teaching. Learning has become the main focus, but does not neglect teaching. Creative children need creative teachers, many activities in campus-level organizations influence and even inhibit their creativity even if they get psychoeducation therapy for creativity. A dilemma is that the most creative child is often punished by parents and teachers who find the behavior difficult to control. Conversely children who fail to manifest curiosity and other creative learning behaviors are stimulated to display these behaviors and are rewarded. The objectives of this study are: 1) Analyzing the effect of teaching on creativity psychoeducation. 2) Analyzing the effect of Activity in organizations on creativity psychoeducation. 3) Analyze teaching on learning creativity. 4) Analyzing the effect of Activity in organizations on learning creativity. 5) Analyzing the effect of psychoeducation of creativity on learning creativity. 6) Analyzing the teaching of learning creativity with the psychoeducation variable of creativity. 7) Analyzing the effect of Activity in organizations on learning creativity with the mediating variable of creativity psychoeducation. This research is descriptive-exploratory-explanatory. The population is semester V students of the academic year 2018/2019 of 38 people. sampling using census techniques. Data collection uses a 5 point Likert Scale questionnaire. Data analysis method uses SmartPLS software v. 3.3.7. From the results of the study it can be concluded as follows: 1) Teaching has a significant effect on the Psychoeducation of creativity 2) Activity in the organization has no effect on the Psychoeducation of creativity 3) Teaching has no effect on learning creativity 4) Activity in the organization has a significant effect on learning Creativity 5) Psychoeducation of creativity has no effect on learning creativity 6) Teaching affects indirectly on learning creativity through creativity psychoeducation 7) Activity in organization indirectly influences learning creativity through creativity psychoeducation.